The Economics of Information - Stigler, George J. (Journal of Political Economy, 1961)
The author systematically examines one of the important issues of information — establishing the market price. He introduces the concept of «search» — where a buyer wanting to get a better price, is forced to question sellers. The article deals with various aspects of finding the necessary information.